Notes on oviposition and demography of a shallow water population of the edible snail Zidona dufresnei (Caenogastropoda: Volutidae) living in San Antonio Bay (northern Patagonia, Argentina) - Pereyra, Patricio Javier (2009)
Zidona dufresnei (Donovan, 1823) is a big-sized and long-lived snail endemic to the south-western Atlantic where it dwells in sandy bottoms between five and 115m; females lay big egg capsules from which crawling juveniles emerge. An unusual population of Z. dufresnei inhabits the low intertidal and shallow subtidal zone of San Antonio Bay, the southernmost location of the species, where it faces many threats. The aim of this study is to describe some of the demographic and reproductive characteristics of this population and to compare them to those located in northern zones. Monthly samples of adults and egg capsules were obtained from October to April and their position was recorded; snails and capsules were gathered for examination in the laboratory. Sex-ratio was near 1:1 for the whole sampling period and the sizefrequency distributions were similar for both sexes; females were wider and heavier than males at the same shell length. Maximum shell length was 120.5mm in our study and so no female reached the minimum size at first gonadal maturity reported for other populations (128mm); female size seems to limit the capsule diameter and the number and size of embryos that are lower than in other populations. Egg capsule and adult densities in the intertidal zone peaked in February and March respectively, averaging 1.34 capsules and 1.91 snails by 100m2 during the sampling period; egg capsule deposition elapsed from November to March and peaked in December; females select cobble by size to lay egg capsules. Due to its restricted distribution and the low juvenile and adult dispersal, the unusual Z. dufresnei population dwelling in San Antonio Bay seems to be quite vulnerable to diverse anthropogenic impacts.